(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Based on examination of specimens of Elatostema J. R. Forster & G. Forster (Urticaceae) from Vietnam, Elatostema albopilosum W.T. Wang var. vicinum L. D. Duan & Y. Lin, a new variety collected from Bac Can Province and Tuyen Quang Province, Vietnam, is described and photographed. This new variety has glabrous stems, glabrous leaves and glabrous peduncles which differs from var. albopilosum that having sparsely puberulent leaf blade on abaxial surface along veins and sparsely strigillose leaf blade on adaxial surface, and short pilose peduncles. E. integrifolium (D. Don) Wedd. and E. pseudodissectum W. T. Wang, two species previously known from Vietnamese adjacent countries, are newly recorded from Ninh Binh Province and Tam Dao National Park, Vietnam, respectively. The vouchers are kept in the Herbarium (PE) of Institute of Botany, Chinese Academy of Sciences, Beijing, China, and their descriptions and photographs are also provided. DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19254 Bangladesh J. Plant Taxon. 21(1): 27-32, 2014 (June)